2020
DOI: 10.1016/j.cmi.2019.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Tracking short-term changes in the genetic diversity and antimicrobial resistance of OXA-232-producing Klebsiella pneumoniae ST14 in clinical settings

Abstract: a b s t r a c tObjectives: To track stepwise changes in genetic diversity and antimicrobial resistance in rapidly evolving OXA-232-producing Klebsiella pneumoniae ST14, an emerging carbapenem-resistant high-risk clone, in clinical settings. Methods: Twenty-six K. pneumoniae ST14 isolates were collected by the Korean Nationwide Surveillance of Antimicrobial Resistance system over the course of 1 year. Isolates were subjected to whole-genome sequencing and MIC determinations using 33 antibiotics from 14 classes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Qin et al reported that the infection incidence of patients who had CRKP colonization in the intestinal tract and nasopharyngeal tract was almost 45.9% in the ICU at Huashan Hospital (Shanghai, China), which posed a true threat to public health because antimicrobial agents are rarely used to treat multidrug- resistant pathogens ( 21 ). Although the environment has been considered a reservoir for pathogens in the ICU and nosocomial outbreaks of OXA-232-CRKP have increased in recent years, there is limited literature reporting on the relationship and transmission of OXA-232-CRKP between the environment and patients ( 9 , 22 , 23 ). In this study, we focused on the OXA-232-CRKP that was first reported by Potron et al in 2013 and then spread throughout the world in recent years ( 12 ), whereas limited literature focuses on colonization in hospitals and patient infections.…”
Section: Resultsmentioning
confidence: 99%
“…Qin et al reported that the infection incidence of patients who had CRKP colonization in the intestinal tract and nasopharyngeal tract was almost 45.9% in the ICU at Huashan Hospital (Shanghai, China), which posed a true threat to public health because antimicrobial agents are rarely used to treat multidrug- resistant pathogens ( 21 ). Although the environment has been considered a reservoir for pathogens in the ICU and nosocomial outbreaks of OXA-232-CRKP have increased in recent years, there is limited literature reporting on the relationship and transmission of OXA-232-CRKP between the environment and patients ( 9 , 22 , 23 ). In this study, we focused on the OXA-232-CRKP that was first reported by Potron et al in 2013 and then spread throughout the world in recent years ( 12 ), whereas limited literature focuses on colonization in hospitals and patient infections.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the ESBL-KP and CRKP have contributed to the emergence of multidrug-resistance strains, diminishing treatment options for patients [ 6 , 11 ]. Furthermore, both resistance ( bla TEM , bla SHV , bla KPC , bla OXA , qnrB1 , oqxA , dfrA12 , sul2 , fosA, and mgrB ) [ 12 ], and virulence genes (iro , kpn , fimH, mrkD , entB , traT , rmpA , fyuA , magA, and hlyA ) [ 13 ] encoded in the bacterium genome played significant factors in the emergence of MDR K . pneumoniae.…”
Section: Introductionmentioning
confidence: 99%
“…Klebsiella pneumoniae ST14, resistant to both carbapenem and colistin, was previously described in South Korea (39). ST 14 was also reported in hospitals from Dubai, United Arab Emirates, which produced OXA-48-type and NDM carbapenemases (40).…”
Section: Discussionmentioning
confidence: 84%